The Little Muslims: An Educational Mobile Game based on Islamic Study Textbook - Mohammad Khaleel Kamarudin; Noorhanifah Murli (Applied Information Technology And Computer Science, 2023)
Little Muslim is an educational mobile application developed for autistic students of Sekolah Kebangsaan Jelapang Jaya. It is aimed to resolve the issue of student limitation to study from textbook and notes at class. This is by providing alternative interactive learning medium to facilitate students learning out of class. The learning content used in Little Muslims is based on Islamic Study for First-Grade and Second-Grade Special Need Student which is the target user. The methodology used for development is Agile which involves planning, implementation, designing, developing, testing, and feedback analysis. The observable results of the project are the application is functioning properly, require low navigational skill from user, and facilitate target student’s retention. The testing result shows that the project was success in both development and its implementation. However, some improvement were required especially in program optimization and wider learning chapter coverage.